Optimizing Financial Outcomes: An Analysis of Individual Investment Decision Factors - Karumuri, Venkateswarlu; Bastray, Tejaswini; Goranta, Laxmana Rao; Rekha, B.; Mary, M.; Joshi, Rajashree; Mahabub Basha, S. (Indian Journal of Information Sources and Services, 2025)
Present study investigates how different demographics' levels of financial literacy, risk tolerance, and investing choices interact with one another. Although previous research has shown a broad relationship between financial literacy and better investing behavior, the exact ways it affects risk tolerance and decision-making remain unknown. There is a dearth of research on the impact of confidence in financial advisers and other demographic variables such as income, gender, education level, and age. This research aimed to capture a broad variety of financial habits by randomly selecting 101 persons based on socio-demographic criteria such as age, gender, marital status, education, profession, and income. The survey was conducted over twenty days in Yelahanka, Bangalore. Findings reveal that 79.2% of respondents earn under ₹2,00,000 annually, and 63.4% save less than 10% of their income, underscoring the challenges individuals face in making significant investments. A significant portion, 48.5%, expressed satisfaction with past investments, but 28.7% were dissatisfied due to poor guidance. Moreover, education correlated with better financial decision-making, but income remains a major barrier to making higher-value investments. The study also found a preference for safer, more liquid investments, with life insurance and gold being popular choices. These insights highlight the critical need for more accessible financial literacy programs and advisory services to address existing gaps and help individuals make more informed, effective financial decisions.